Evaluation of the extrinsic characterization layer of zirconium-infiltrated lithium silicate glass ceramic - Teixeira , Lara Viégas Faria; Souza, Karina Barbosa; Barreto , Larissa Araújo Lopes; Demachkia , Amir Mohidin; Rossi, Natália Rivoli; Paes Junior, Tarcisio José de Arruda (Brazilian Dental Science, 2025)
Objective: To evaluate the effects of the extrinsic characterization process on the optical properties and roughness of zirconium-infiltrated lithium silicate glass-ceramic. Material and Methods: Twenty-four Disc-shaped samples (Ø=12 mm and 1.2 mm in thickness) were divided into two groups (n=12): “Without Characterization” (C) – control group, and “With Characterization” (CC). Surface topography (Ra) was analyzed using a contact profilometer, color and translucency were evaluated using a spectrophotometer. The samples were subjected to aging in red wine for 15 minutes over 30 days. After aging, the tests were repeated. Two-way ANOVA, and Tukey’s 5% test were applied to roughness and translucency. The Kruskal-Wallis and Dunn’s tests were used for color analysis. Results: Roughness (Ra), color variation, and translucency were statistically affected only by the “characterization” factor (p<0.001). The CC group exhibited the highest Ra values and the greatest color variations, before and after aging. The C group, with and without aging, presented the highest translucency values. Conclusion: It was observed that characterization influenced color variations, translucency and increased the surface roughness before and after aging. Aging in red wine did not significantly affect color variation or translucency; however, it resulted in a color alteration that can be clinically perceptible. Clinical relevance: While the characterization process enhances the aesthetic customization of restorations, clinicians should be aware that it may lead to increased roughness and greater susceptibility to clinically perceptible color changes over time. These findings highlight the need for careful selection and application of characterization protocols to balance aesthetics and material longevity. KEYWORDS Ceramics; Color; Dental Materials; Glass ceramics; Surface roughness.